PENGENDALIAN PERSEDIAAN MELALUI PENENTUAN PRODUK STRATEGI - Nurul Dzikrillah; Humiras Hardi Purba; Dhonny Suwazan; Noer Wahjoedi (Universitas Indraprasta PGRI, 2016)
Quality improvement and costs control are vital to organizations for work performance enhancement and fulfilling customers’ requirement. Inventories that are stored in large amount of quantities will result in waste. It is a significant job for the inventory control personnel to select an appropriate policy and maintain an optimum level of inventory. The selection of inventory policy is very much important in the current scenario of intensive global competition and dynamic nature. The aim of this study is to reduce inventory value by determining strategy of each product. Inventory model classification was done based on production planning and total pending order. The result is inventory value reduce by the end of the year in 11.3 million USD which is achieve the target. The target was locked in 1.5 million USD. DIO value is 75 days by the end of the year. Key Word: inventory, inventory model classification, product strategy, inventory proection